SOSIALISASI LITERASI DAN IMPLEMENTASI PRODUK PERBANKAN SYARIAH DI NAGARI BATANG ARAH TAPAN, KEC. BASA AMPEK BALAI TAPAN - Maulida Hafni; Ahmad Khairul Nuzuli; Winda Oktaviana (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2023)
Community service activities at Posko 35 Batang Arah Tapan aim to provide Islamic banking literacy related to regulations, systems and products from Islamic banking. The methods used in carrying out this activity are lectures, implementing and discussion sessions. Community service activities apply three sessions, namely session one exposure on service activities, session two exposure on entrepreneurship and session three exposure to material on Islamic banking financing. Community service activities at Posko 35 Batang Arah Tapan were carried out in Nagari Batang Arah Tapan, Basa Ampek District, Balai Tapan. The results of this community service activity are literacy socialization and implementation activities that have an impact on increasing sharia financial and banking education. The author and the KKN team at Posko 35 Batang Arah Tapan fully understand and understand the regulations, systems and various savings products, financing and services available in Islamic banking. These findings show the importance of more intensive socialization in order to increase banking literacy and implementation in a complex society.